Identification Of Students Of Misconception Junior High School Class VII Sutera On The Topic Photosintesis Using Two Tier Diagnostic Test - Nining Efriani; Zulyusri Zulyusri; Yosi Laila Rahmi; Ramadhan Sumarmin (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Misconception is a wrong concept because it bring contradicts concept with experts concept. Misconception occur because students develop their own understanding based on experience, what they seeing and hearing, to understand a concept. Misconceptions that occur in students, before repairs must be identified first. The purpose of this study was to determine students' misconceptions about photosynthesis in Class VII Sutera junior High School. The sample of this research was 40 students of class VII. This type of research is descriptive. The technique using diagnostic test two-tier multiple choice. Test diagnostic used to identify student errors because it can measure 2 levels of high-level thinking skills, scoring is easy, fast and objective, and the opportunity for students to guess answers less. Based on the results of the study, it was found that the highest misconception was found in organisms that could carry out photosynthesis at 87.5%, organs that played a role in photosynthesis 44.5%, photosynthetic processes 42.5%, experiments with photosynthetic processes 25%, and factors affect photosynthesis 38.125%. Thus it can be concluded, that there is a misconception in Class VII Sutera Junior High School about photosynthetic material with varying percentages.